23 UPH in Africa, process and progress - (:unkn) unknown (My University, 2022)
Following the 23 Unsolved Problems in Hydrology paper (Blöschl et al. 2019), we launched the "23 UPH in Africa" initiative in collaboration with the UNESCO/IHP FRIEND-Water Programme, the ICIREWARD UNESCO Cat 2 Centre of Montpellier and the IAHS-ICSW commission. This consultation aims to identify and review the considerable research coming out of Africa lately, and put forward the contribution of the African academic community to advancing key unsolved problems in hydrology. So far, more than 400 colleagues working in 26 countries registered their interest, and filled in a brief online questionnaire, created to gather and synthesise key information about interested participants. A call for volunteers led to selecting 42 colleagues to coordinate discussions within the seven UPH themes and 23 questions. Using online platforms and collaborative tools, these working groups seek to highlight essential research and results from Africa contributing to the 23 UPH. The synthesis also underlines the specific insights and advances related to the African physical and socio-economic environment, as well as priority and emerging questions from the continent.
Keywords: African Research